2017
DOI: 10.1001/jamaophthalmol.2017.3292
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Microstructural Changes of the Retina in Infants With Congenital Zika Syndrome

Abstract: IMPORTANCE A better pathophysiologic understanding of the neurodevelopmental abnormalities observed in neonates exposed in utero to Zika virus (ZIKV) is needed to develop treatments. The retina as an extension of the diencephalon accessible to in vivo microcopy with spectral-domain optical coherence tomography (SD-OCT) can provide an insight into the pathophysiology of congenital Zika syndrome (CZS).OBJECTIVE To quantify the microstructural changes of the retina in CZS and compare these changes with those of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…To corroborate Zhao et al's 31 findings, in a most recent study, Aleman et al 32 provided the first in vivo evidence in humans showing a thinning of the ganglion cell layer, which suggests an in utero depletion of this neuronal population as a consequence of ZIKV infection.…”
Section: Pathophysiology Of Ocular Findingsmentioning
confidence: 74%
“…To corroborate Zhao et al's 31 findings, in a most recent study, Aleman et al 32 provided the first in vivo evidence in humans showing a thinning of the ganglion cell layer, which suggests an in utero depletion of this neuronal population as a consequence of ZIKV infection.…”
Section: Pathophysiology Of Ocular Findingsmentioning
confidence: 74%
“…The virus could reach the fetal circulation from the placenta and infect the RPE, retinal endothelial cells, and the retina [ 94 ]. The other possible pathway would be through axonal transport into the eye along the optic nerve [ 95 , 96 ], leading to ganglion cell layer (GCL) loss, foveal maldevelopment, and central chorioretinal abnormalities [ 97 ]. How ZIKV and other flaviviruses enter the eye in vivo remains to be determined.…”
Section: Experimental Models Of Ocular Zikv Complicationsmentioning
confidence: 99%
“…For example, Singh et al have recently reported that retinal cell types lining the BRB are susceptible to ZIKV infection and cause cell death by activating Caspase 3 [ 94 ]. Zhao et al and Aleman et al have independently shown the Muller glia cells to be the primary target of ZIKV infection leading to decreased neurotropic functions and increased pro-inflammatory cytokines post infection with the help of murine models [ 96 , 98 ]. ZIKV infection in RPE was shown to disrupt its cell to cell adhesion and barrier properties [ 99 ].…”
Section: Experimental Models Of Ocular Zikv Complicationsmentioning
confidence: 99%
“…A separate imaging analysis software (http://imagej.nih.gov/ij/links.html, available in the public domain) was used to generate longitudinal reflectivity profiles from exported images and help supervise and correct automatic segmentation errors. [18][19][20] ''Retinal thickness'' was defined as the distance between the signal peak at the vitreoretinal interface (the internal limiting membrane [ILM]) and the posterior boundary of the major signal peak that corresponds to the basal retinal pigment epithelium/Bruch's membrane complex (RPE/BrM). In normal subjects, the RPE/BrM is the last reflectivity within the 4-6 signals that are identifiable in the outer retina.…”
Section: Retinal Imagingmentioning
confidence: 99%